2002
DOI: 10.1046/j.0269-283x.2002.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative insecticidal power of three pyrethroids on netting

Abstract: Abstract. Adult mosquitoes, Anopheles gambiae Giles and Culex quinquefasciatus Say (Diptera: Culicidae), were exposed for 3 min to replicate samples of polyester netting cut from replicate bednets treated with pyrethroid insecticide formulations at the recommended concentration (alphacypermethrin SC at 40 mg ai=m 2 ; cyfluthrin EW at 50 mg ai=m 2 ; deltamethrin WT at 25 mg ai=m 2 ), or treated with only a quarter of those dosages. After 4 months domestic use of the bednets in Malawi, chemical assays showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…This is, however, in keeping with results reported in the literature for alpha-cypermethrin. Adams et al [21] tested low doses of various insecticides in Malawi and demonstrated that even a dose of only 6.5 mg/m 2 alpha-cypermethrin resulted in a 93% mortality rate in Anopheles gambiae s.s . Similarly high bio-assay results were obtained by Graham et al in Pakistan [22] after 21 washes and a target dose of 15 mg/m 2 achieving a 49% mortality rate for Anopheles stephensi .…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, in keeping with results reported in the literature for alpha-cypermethrin. Adams et al [21] tested low doses of various insecticides in Malawi and demonstrated that even a dose of only 6.5 mg/m 2 alpha-cypermethrin resulted in a 93% mortality rate in Anopheles gambiae s.s . Similarly high bio-assay results were obtained by Graham et al in Pakistan [22] after 21 washes and a target dose of 15 mg/m 2 achieving a 49% mortality rate for Anopheles stephensi .…”
Section: Discussionmentioning
confidence: 99%
“…activity after just a few washes with soap or detergent Miller et al, 1991Miller et al, , 1995Pleass et al, 1993;Jawara et al, 1998;Vythilingam et al, 1999;Adams et al, 2002;Gonzalez, 2002;Kayedi, 2004;Graham et al, 2005). Although nets that have lost most of their insecticide after repeated washing can be successfully retreated, the observed frequencies of such re-treatment, when the nets are in routine use in the field, have generally been found to be very low (Aikins et al, 1994;Cheng et al, 1995;Elissa and Curtis, 1995;Jana-Kara et al, 1995;Curtis, 1996;Lengeler et al, 1996;Lines, 1996;Cham et al, 1997;Kroeger et al, 1997;Winch et al, 1997;Kachur et al, 1999;Miller et al, 1999;Clarke et al, 2001;Kalmolratanakul et al, 2001;Schellenberg et al, 2001;Maxwell et al, 2002;Curtis et al, 2003;Kayedi, 2004).…”
mentioning
confidence: 99%
“…kdr R resistance is caused by mutations in the sodium channel: leucine to phenylalanine substitution, originally observed in West Africa [31], and leucine to serine mutation in East Africa [32]. Recently, a new mutation in the sodium channel associated with kdr-west mutation conferring additional resistance to DDT and permethrin [33] was reported [34]. Experimental studies conducted in Southern Benin and in South Africa respectively with lambdacyhalothrin [33] on bednets and with deltamethrin [33] through indoor residual house spraying [35] suggested that PYRs resistance may have contributed to the failure of vector control endeavours in these areas [21,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%